Analysis Of Factors Causing The Occurrence Of Type 2 Diabetes Mellitus At Medan Denai Health Center - Agustia, Dilma'aarij; Br Gultom, Ria Fazelita; Nainggolan, Wiwiek Elsada; Khoiriyah, Fitri; Hidayati, Yusmalia; Lubis, Dita Anggriani (Jurnal Ilmu Sosial Mamangan, 2024)
Background: Type 2 diabetes mellitus is one of the most common chronic diseases in the world. Treatment of diabetes mellitus requires a long time and even a lifetime to reduce complications that lead to death. The causes of diabetes mellitus are very complex and many factors accompany it. The factors that cause diabetes mellitus need to be known to reduce the presence of new diabetes mellitus in the future. This study aims to determine the factors that cause diabetes mellitus, especially type 2 diabetes mellitus at the Medan Denai Health Center. Methods: This study used a quantitative research design with secondary data in 2023 using cross sectional analytic methods. The population was all patients with type 2 diabetes mellitus and the technique of taking total sampling with a total of 50 respondents. Analysis using univariate analysis and logistic regression. Results: Type 2 diabetes mellitus patients who have comorbidities are mostly suffering from hypertension as many as 22 (44%) respondents, and the results of logistic regression analysis show that there is a statistical influence on the presence of comorbidities on the incidence of Type 2 diabetes mellitus cases at Medan Denai Health Center (OR = 0.27, 95% CI = 0.08-0.90, p-value